Decentralization in Turkey - Yıldırım, Galip Emre, author. aut Link Link
1 online resource.
Keywords: "This book explores the political dimensions of decentralization and (re)centralization policies in Turkey over the past century. It traces the evolution of these policies, from the late Ottoman Empire's decentralization efforts in the late 19th century, to the centralization under the Kemalist regime in the early 20th century, followed by the limited decentralization of the 1960s and 1980s, and the decentralization and recentralization policies of the Erdoğan governments over the past two decades. The book seeks to answer why and how decentralization efforts have repeatedly failed in Turkey. What sets this work apart is its innovative theoretical and empirical approach to Turkish politics. By framing decentralization as a political rather than a technical issue, the book draws on historical institutionalism, "bringing the state back in" theory, and path dependency to offer fresh insights. It also presents a wealth of empirical data based on archival research from French and Turkish sources, as well as interviews with Turkish local actors. On a broader scale, the book helps readers understand a key paradox in Turkish politics: how ruling elites use centralization as a policy tool while also pursuing limited decentralization. Bringing together a variety of theoretical and empirical perspectives, this work will be of great interest to students and scholars of Turkish studies and serves as a strong example of area studies research"-- Provided by publisher.